PUTUSAN ULTRA PETITUM PARTIUM PERKARA PERDATA DITINJAU DARI PASAL 178 AYAT (3) HIR (Studi Kasus Putusan Nomor 445/Pdt.G/2018/PA. Kab. Mn) - Fadhli, Risma Safitri (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractCivil procedural law recognizes the principle of Ultra petitum partium as referred to in article 178 paragraph (3) of the HIR which states that